2013
DOI: 10.18632/oncotarget.1131
|View full text |Cite
|
Sign up to set email alerts
|

LIN28A facilitates the transformation of human neural stem cells and promotes glioblastoma tumorigenesis through a pro-invasive genetic program

Abstract: The cellular reprogramming factor LIN28A promotes tumorigenicity in cancers arising outside the central nervous system, but its role in brain tumors is unknown. We detected LIN28A protein in a subset of human gliomas observed higher expression in glioblastoma (GBM) than in lower grade tumors. Knockdown of LIN28A using lentiviral shRNA in GBM cell lines inhibited their invasion, growth and clonogenicity. Expression of LIN28A in GBM cell lines increased the number and size of orthotopic xenograft tumors. LIN28A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
76
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 68 publications
(80 citation statements)
references
References 47 publications
4
76
0
Order By: Relevance
“…Notably, although we observed cytoplasmic LIN28 expression uniformly (100 %) in C19MC amplified CNS-PNETs, our analyses also revealed cytoplasmic as well as nuclear LIN28 staining in a subset of MBs, ATRTs, EPNs and HGGs but not CPCs. Similar to prior reports of cytoplasmic LIN28 staining in 20–60 % of pediatric and adult gliomas [15] and 64 % of ATRTs [3], we observed strong LIN28 cytoplasmic staining in up to 20–25 % of ATRTs and HGGs analyzed (Supplemental Tables 1, 3), which contrasts with a report of cytoplasmic LIN28 immunostaining exclusively in ETANTRs [11]. The reason underlying these discrepant observations is unclear and may be related to the limitations of tissue microarray analyses to comprehensively capture tumor heterogeneity.…”
Section: Discussionsupporting
confidence: 91%
“…Notably, although we observed cytoplasmic LIN28 expression uniformly (100 %) in C19MC amplified CNS-PNETs, our analyses also revealed cytoplasmic as well as nuclear LIN28 staining in a subset of MBs, ATRTs, EPNs and HGGs but not CPCs. Similar to prior reports of cytoplasmic LIN28 staining in 20–60 % of pediatric and adult gliomas [15] and 64 % of ATRTs [3], we observed strong LIN28 cytoplasmic staining in up to 20–25 % of ATRTs and HGGs analyzed (Supplemental Tables 1, 3), which contrasts with a report of cytoplasmic LIN28 immunostaining exclusively in ETANTRs [11]. The reason underlying these discrepant observations is unclear and may be related to the limitations of tissue microarray analyses to comprehensively capture tumor heterogeneity.…”
Section: Discussionsupporting
confidence: 91%
“…Recently, high levels of both Lin28A and Lin28B were also observed in high-grade gliomas and associated with invasiveness and proliferation (Mao et al, 2013). We also observed that several mesenchymal markers were strongly reduced upon Ezh2 depletion in glioblastoma, whereas epithelial markers were upregulated.…”
Section: Discussionsupporting
confidence: 60%
“…Orthotopic injections were performed after anesthesia with ketamine/xylazine, as previously described (25). Coordinates for brainstem injections were −5 from bregma, 1 to right, and 3.5 deep.…”
Section: Methodsmentioning
confidence: 99%